Arahan Pengembangan Identitas Kawasan Permukiman Pesisir Sebagai Pembentuk Citra Kawasan - Tri Ambarwati; Shirly Wunas; Mimi Arifin (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
City and regional identity is an image formed from the biological rhythm of a particular place or space that reflects time (sense of time), and grows rooted from the social, economic, and cultural activities of the city itself. Regional identity can be an attraction and improve the economy of the region. This study aims to identify physical conditions that can form the identity of coastal settlements, optimize elements to develop the image of coastal settlements, and develop strategic directions that can shape the identity of coastal settlements. Data collection methods carried out include observation, interviews, documentation, and literature studies. The analytical method used is comparative analysis and spatial descriptive analysis. The results of this study are elements that form the city image found in the case study in Ujung Tanah district, Makassar City such as landmarks, paths, edges, and node. Furthermore, the elements for developing residential imagery in terms of social aspects can be seen in social interaction activities and from the economic aspects seen in the fish processing home industry. Finally, the direction for the development of the physical identity of the area is based on related rules or theories that focus on these four elements and the direction of non-physical development that focuses on socio-economic aspects.